What is 'policy' and what is 'policy response'? An illustrative study of the implementation of the Leadership Standards for Social Justice in Scotland. (January 2016) - Ward, SC; Bagley, C; Lumby, J; Hamilton, T; Woods, P; Roberts, A
This article examines 'policy' and 'policy response' through documentary analysis and an illustrative study of policy implementation. Our approach is informed by Foucault's (2009) theory that power relations in society are conditioned by a culturally generated set of ideas, and that these relations contain the space for both coercion and resistance. Our aim is to consider the potential for policy compliance and contestation by: (1) describing policy and policy response, drawing attention to the neoliberal hegemony that has come to dominate policy discourse globally; and (2) considering how social agents respond to a particular instance of policy. We provide documentary analysis of the interpolation of leadership into policy development in Scotland following the OECD (2007) report, and offer a small scale illustrative study of the implementation of the Leadership Standards for Social Justice in Scotland (GTCS, 2012). The head teachers in our study drew upon the discourse of marketization when describing their response to policy on social justice. We consider this finding in light of the argument that our interaction with policy has been conditioned through previous instances of neoliberal discourse formation (Ball, 2008). We conclude by considering the implications of the neoliberal hegemony for policy debate.